2020
DOI: 10.29342/cnj.v3i1.106
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Klinis Dan Derajat Berat Gejala Motorik Penyakit Parkinson Di Rsup Sanglah Dan Rsud Wangaya Denpasar

Abstract: Background: Parkinson's Disease (PD) is the second most common neurodegenerative disorder. The Global Burden Disease (GBD) report published in 2018 estimated there were 6.1 million individuals suffering from PD globally and causing 3.2 million Disability-Adjusted Life Years (DALY) and 211,296 deaths in 2016. Disability mainly caused by motor symptoms. This study aims to determine the clinical characteristics and motor severity in PD patients in Sanglah and Wangaya General Hospital Denpasar. Method: Descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…13 The results of this study also did not show a correlation between HDL and PD. [13][14][15][16][17][18][19] However, the results of this study are different from the results of research conducted by Agustin et al in Yogyakarta in 2017 which showed no significant difference in LDL levels to the severity of PD based on the H and Y scale. 11 The difference in the results of this study is due to the fact that there are many factors that can changes the mechanism and pathophysiology of dopaminergic cells in patients with PD that affect disease progression and the differences in the statistical test methods of this study with those of Agustin et al The effect of cholesterol levels on the biologic progression of PD is unknown, but it has been suggested that cholesterol may facilitate the repair of injured neuronal pathways in Parkinson's disease.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…13 The results of this study also did not show a correlation between HDL and PD. [13][14][15][16][17][18][19] However, the results of this study are different from the results of research conducted by Agustin et al in Yogyakarta in 2017 which showed no significant difference in LDL levels to the severity of PD based on the H and Y scale. 11 The difference in the results of this study is due to the fact that there are many factors that can changes the mechanism and pathophysiology of dopaminergic cells in patients with PD that affect disease progression and the differences in the statistical test methods of this study with those of Agustin et al The effect of cholesterol levels on the biologic progression of PD is unknown, but it has been suggested that cholesterol may facilitate the repair of injured neuronal pathways in Parkinson's disease.…”
Section: Discussioncontrasting
confidence: 94%
“…Only 6.7% of patients came with stage H and Y IV and 1.7% H and Y V, this may be explained by limited patient mobility so that patients do not come routinely to the clinic for control. 15,16 Some PD patients in this study used more than two drugs (53.33%). Several previous studies obtained almost have the same results by Oktariza et al in Bandung whereas patients usually consume more than two types of drugs (54.54%) and Agustin et al in 2017 in Yogyakarta the majority of patients used two types of Parkinson's drugs (60%).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations